The Effect of Digital Marketing, Store Atmosphere, and Product Quality on Purchase Decision - Muhammad Umar A (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
The growing intensity of competition in the culinary industry demands the implementation of an integrated marketing strategy, which serves as the focus of this research. This study aims to determine the influence of digital marketing, store atmosphere, and product quality on consumer purchasing decisions at the Wizzmie Restaurant in Palu City. This study uses a quantitative approach with descriptive and verification methods. Data were collected through closed questionnaires distributed to 80 respondents selected using a purposive sampling technique, with the criteria being consumers who have eaten directly at the restaurant and are at least 17 years old. The data analysis technique used is multiple linear regression to test the influence of each variable on purchasing decisions partially and simultaneously. The results show that digital marketing, store atmosphere, and product quality have a significant influence on consumer purchasing decisions. Digital marketing is effective in building brand awareness and reaching a wider market. Store atmosphere provides physical and emotional comfort that encourages purchasing decisions, while product quality plays an important role in creating consumer satisfaction and loyalty. These findings indicate that strategic and sustainable integration of these three aspects can create a comprehensive consumer experience and encourage increased purchasing decision.